2015
DOI: 10.1136/bmjqs-2015-004448
|View full text |Cite
|
Sign up to set email alerts
|

A behaviourally anchored rating scale for evaluating the use of the WHO surgical safety checklist: development and initial evaluation of the WHOBARS

Abstract: We have developed a generic instrument for comprehensively rating the administration of the SSC and informing initiatives to realise its full potential. We have provided data supporting its capacity for discrimination, internal consistency and inter-rater reliability. Further psychometric evaluation is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…Twenty OR teams comprising a consultant surgeon, surgical registrar, anaesthetist, anaesthetic technician, circulating nurse and scrub nurse took part in three simulated scenarios during the day-long MORSim course 42. Participants were from two different hospitals but on any given day the team was from one site and so were more likely to have worked together before and work together again soon after the course.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty OR teams comprising a consultant surgeon, surgical registrar, anaesthetist, anaesthetic technician, circulating nurse and scrub nurse took part in three simulated scenarios during the day-long MORSim course 42. Participants were from two different hospitals but on any given day the team was from one site and so were more likely to have worked together before and work together again soon after the course.…”
Section: Methodsmentioning
confidence: 99%
“…Checklists themselves are clearly valuable tools, but not sufficient on their own. The way in which they are administered by staff may lead to an effective communication between team members or an unhelpful exercise in compliance 41 42…”
mentioning
confidence: 99%
“…The formerly developed behavioral marker systems to assess surgical team´s non-technical skills include some exemplar behaviors that are related to nursing sub-team and circulating nurse´s nontechnical skills (24)(25)(26)(27)(28)(29)(30). Only one ethnographic study (11) has been conducted to extract the circulating nurse´s non-technical skills; however, the study not reported exemplar behaviors, so we studied the references that are related to nursing and operating room to extract more behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…The adapted Human Factors Attitude Questionnaire has a five‐point Likert scale response format and is used widely to measure organizational safety culture. The WHO Behaviourally Anchored Rating Scale (WHOBARS) is a validated tool that assesses non‐technical skills during checklist administration. For each part of the checklist (sign in, time out, sign out), WHOBARS evaluates five domains on a scale from 1 to 7: setting the stage, team engagement, communication activation, communication of problem anticipation, and communication of process completion.…”
Section: Methodsmentioning
confidence: 99%